Social Media in Education - Anaraki, Firouz; Dadras, Mohammadamin; Arun Pinto, Colin; Manomat , Tatphichar; Amirkhani, Mahdi (International Journal of Multidisciplinary in Management and Tourism, 2024)
This article aimed to provide educators and students with an opportunity to engage learners in the online classroom, as well as to support development of learner skills and competencies using social media. Social media is basically a structure that consists of individuals, communities, companies, organizations or classes in universities with similar interests, attitudes, values, lifestyles, visions, friendships, and learning objectives in the field of online learning, this structure can be used in various ways and through a number of tools. This paper tries to study some of the popular social media such as Facebook, X, LinkedIn, and YouTube and see how they could be utilized in e-Learning.